Human Centered Design Process of Health Monitoring Device under EPICS - Sharanya, G.; Sai Abhishek, C.; Manikanth Reddy, K.; Unissa, Azeem (Journal of Engineering Education Transformations, 2018)
This paper describes about the whole design process (human centred design process) of ’Health Monitoring device’ under EPICS (engineering projects in community services). It was initialised in December 2016 by EPICS partnering with "YOUTH FOR SOCIAL WELFARE SOCIETY". The project is designed for our client Mr. Chikile Madhu babu, head of the organisation. "Health monitoring device" can help patients and elderly people to monitor their health condition. The people, who cannot go to hospitals or health camps, can use this device to check their health status. The device is capable of measuring blood pressure, ECG, pulse rate, body temperature and room temperature. It is portable, accurate and easy to use.